Teacher Supervisor Assessment Process Level I (IV/b) and above at the Aceh Provincial Education Quality Assurance Institute - Ismail; Thaib, Anwar; Gunawan (Dinasti Publisher, 2023)
The government makes efforts to prepare teachers and also makes efforts to provide guidance for teachers in carrying out teaching duties. One of these guidance efforts is to prepare for promotion by determining the number of credit points periodically. In this case, there are several rules that must be met by teachers so that promotion can be carried out through assessment with a credit point system. Currently, the average teacher has the ranks of Level I Arranger (III/d), Supervisor (IV/a), and Level I Supervisor (IV/b), to achieve the ranks above, of course there is a process that must be gone through, namely submitting a proposal for promotion to an official institution that has been appointed by the government to handle the process. The formulation of the problem in this study is how the Assessment Process for Level I Supervisor Teachers (IV/b) and above at the Aceh Provincial Education Quality Assurance Institute, and what obstacles are faced in the assessment process for level I supervisor teachers (IV/b) and above at the Aceh Provincial LPMP to support the role of the Integrated Service Unit at the Aceh Provincial LPMP for Educators and Education Personnel. In this study, the researcher used a descriptive qualitative method, data validity techniques with triangulation techniques. Triangulation technique, namely researchers use different data collection techniques to obtain data from the same source. The data collection techniques in question are interviews, observations, and documentation where the data source is primary data from research informants. The results of the study indicate that the Assessment Process for Level I (IV/b) and above Teacher Supervisors at the Aceh Province LPMP from the perspective of its duties and functions has not been maximized, due to lack of socialization, very limited human resources, and obstacles in the Assessment Process for Level I (IV/b) and above Teacher Supervisors are also still very many, such as differences in credit scores in PAK and SKKP, there are still many things that need to be fixed so that the desired results can be achieved optimally.